Chemical Composition of Mudaffara Cheese Manufactured by Solanum dubium Coat Extract and Chymosin (Journal of Veterinary Medicine and Animal Production, 2021)
This study was conducted to determine the chemical composition of Mudaffara cheese manufactured by Solanum dubium coat extract and chymosin as coagulant enzymes. Mudaffara cheese was manufactured from warmed (35ºC) raw cow milk to which a starter culture (2% w/w of 1:1 combination of Streptococcus thermophilus and Lactobacillus bulgaricus) was added. In the first treatment, chymosin extract (20 ml /10 L milk) was added, while in the second treatment Solanum dubium coat extract (20 ml / 10 L milk) was added. After coagulation, whey was drained and curd was cut and placed in an incubator at 40ºC for 3 hours, followed by cooking at 75ºC for 5 min. Black cumin (0.5% w/w) was added to the curd and braided into the final form. The curd was preserved in the salted whey (10% w/w) for 24 hours and then the cheese was preserved at 4ºC for 28 days. Chemical analysis was carried out at day 1, 7, 14, 21 and 28. The results showed that all chemical components under study were not significantly affected by the type of coagulant except fat content which was significantly (P
Keywords: Mudaffara cheese; chemical; chymosin; Solanum dubium; storage period